PENGARUH EFIKASI DIRI,BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL SEKRETARIAT DAERAH KABUPATEN GAYO LUES - Nur baya; Muhammad Basyir (Departemen Manajemen, 2019)
This study aims to determine and explain the effect of self-efficacy on employee performance in Gayo Lues Regency. The variables used in this study are self-efficacy, organizational culture and job satisfaction on employee performance. The population in this study is the gayo lues district secretariat. The sample was taken as many as 111 respondents. Hypothesis testing uses multiple regression analysis with the help of SPSS 22 for Windows. The results showed that self-efficacy, and job satisfaction had a significant effect both simultaneously and partially on employee performance. This study has limitations including the limited object of research and is expected in future studies to test different research objects. Therefore stakeholders in the Regional Secretariat of Gayo Lues Regency are expected to pay more attention to Employees through increasing attraction activities or Performance capabilities to attract Employees' interest to give the impression of pleasure in work, increase the development of gayo lues district secretariat creativity both facilities and infrastructure that must be held by stakeholders Secretariat Derah Gayo Lues Regency